A Medical History of Hong Kong : 1842-1941 - Chan-Yeung, Moira (Book collections on Project MUSE., 2018)
This book tells the fascinating story of the development of medical and sanitation services in Hong Kong during the first century of British rule and how changing political values and directions of the colonial administration and the socioeconomic status of the Hong Kong affected the policies of development in these areas. It also recounts how the bubonic plague of 1894 changed the government's laissez-faire attitude towards sanitation and public health and began sanitary reforms and developed public health infrastructure.